The 2015 Gorkha earthquake investigated from radar satellites: slip and stress modeling along the MHT - Diao, Faqi; Walter, Thomas R.; Motagh, Mahdi; Prats-Iraola, Pau; Wang, Rongjiang; Samsonov, Sergey V. (Frontiers in Earth Science, 2015)
The active collision at the Himalayas combines crustal shortening and thickening, associated with the development of hazardous seismogenic faults. The 2015 Kathmandu earthquake largely affected Kathmandu city and partially ruptured a previously identified seismic gap. With a magnitude of Mw 7.8 as determined by the GEOFON seismic network, the 25 April 2015 earthquake displays uplift of the Kathmandu basin constrained by interferometrically processed ALOS-2, RADARSAT-2 and Sentinel-1 satellite radar data. An area of about 7,000 km² in the basin showed ground uplift locally exceeding 2 m, and a similarly large area (approx. 9000 km2) showed subsidence in the north, both of which could be simulated with a fault that is localized beneath the Kathmandu basin at a shallow depth of 5-15 km. Coulomb stress calculations reveal that the same fault adjacent to the Kathmandu basin experienced stress increase, similar as at sub-parallel faults of the thin skinned nappes, exactly at the location where the largest aftershock occurred (Mw 7.3 on 12. May, 2015). Therefore this study provides insights into the shortening and uplift tectonics of the Himalayas and shows the stress redistribution associated with the earthquake.